The Self-Regulated Learning dan Prokrastinasi Akademik Pada Siswa - Anita Dwi Agustina (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
The background of this research is the high academic procrastination behavior and low self-regulated learning in XI grade students of MA Futuhiyyah Kudu Semarang. Based on the AKPD results, it shows the highest need in the personal and learning fields. The purpose of this study is to finding the relationship between self-regulated learning and academic procrastination in XI grade students of MA Futuhiyyah Kudu Semarang. This research uses quantitative research with a correlational research design. The participants of this research was 68 students using a saturated sampling technique. The data collection of this study used the academic procrastination scale and the self-regulated learning scale. The results of the study with the Pearson product moment correlation test, obtained a correlation value of r count -0.326. While the r table value for the number of samples with 45 samples with a significance level of 5% was obtained at 0.294. Therefore, the value of r count is 0.326 > r table is 0.294, it can be concluded that there is a significant relationship between self-regulated learning and academic procrastination of class XI students at MA Futuhiyyah Kudu Semarang. Keywords: Self-Regulated Learning, Academic Procrastination